Osteopontin and Osteoprotegerin as Potential Biomarkers in Abdominal Aortic Aneurysm before and after Treatment. (9th July 2014) - Filis, Konstantinos; Martinakis, Vasilios; Galyfos, George; Sigala, Fragiska; Theodorou, Dimitris; Andreadou, Ioanna; Zografos, Georgios
Abstract : Aim. Although osteopontin (OPN) and osteoprotegerin (OPG) have been associated with abdominal aortic aneurysms (AAAs), no association of these two biomarkers with AAA surgical or endovascular treatment has been reported. Material and Methods. Seventy-four AAA patients were prospectively selected for open or endovascular repair. All aneurysms were classified (Types A–E) according to aneurysmal extent in CT imaging (EUROSTAR criteria). All patients had preoperative serum OPN and OPG values measurements and 1 week after the procedure. Preoperative and postoperative values were compared with a control group of twenty patients (inguinal hernia repair). Results. Preoperative OPN values in patients with any type of aneurysm were higher than in the control group, while OPG values showed no difference. Postoperative OPN values in AAA patients were higher than in the control group. OPN values increased after open surgery and after EVAR. OPG values increased after open surgery but not after EVAR. There was no difference in OPN/OPG values between EVAR and open surgery postoperatively. Conclusions. OPN values are associated with aneurysm presence but not with aneurysm extent. OPG values are not associated either with aneurysm presence or with aneurysm extent. OPN values increase after AAA repair, independently of the type of repair.